Neutrophil-to-lymphocyte ratio in type 2 diabetes patients combined with Lower Extremity Peripheral Artery Disease - Li, Li; Wang, Mengjie; Jia, Ting; Jiang, Xiaowan; Yang, Fan; Wang, Zhongjing; Zhang, Xuyan (Frontiers in Endocrinology, 2024)
Objective: This study explored the utility of NLR (neutrophil-to-lymphocyte ratio) as a marker to predict Lower Extremity Peripheral Artery Disease (PAD) in the Chinese population, as well as to assess its consistency and diagnostic value with digital subtraction angiography. Methods: Patients were distributed into three groups according to the angiography in lower limb arte rial: group L1, plaque with no stenosis; group L2, plaque with luminal stenosis and group L3, total va scular occlusion. Changes in the neutrophil-to-lymphocyte ratio were documented and compared amo ng groups.Results: Compared to group L1, NLR was significantly increased in L2 (1.76 vs 2.35, p=0.037) and L3 (1.76 vs 3.60, p<0.001), with a gradual decrease in ABI (Ankle-Brachial Index, 1.11 vs 1.02 vs 0. 94, p<0.001) . Those older patients with higher prevalence of hypertension (p=0.002) , obesity (p=0. 032), or reduced high-density lipoprotein cholesterol (p=0.020) were more likely to develop PAD; hi gher glycosylated hemoglobin (p=0.045), low-density lipoprotein cholesterol (p=0.006), and systolic blood pressure (p<0.001) levels led to a greater tendency to suffer stenosis or even occlusion; the pro bability of severe stenosis (>70%) increased to 2.075 times for every 1 increase in NLR, while it was 46.8% for every 0.1 increase in ABI. The optimal NLR cut-off value to predict severe stenosis in PA D was 2.73 . Receiver operating characteristic curve analysis of the inflammatory biomarkers and sev ere stenosis prediction displayed an area under the curve of 0.81.Conclusions: NLR could serve as a new noninvasive and accurate marker in predicting PAD.